The Long-Term Development of Training, Technical, and Physiological Characteristics of an Olympic Champion in Nordic Combined - Rasdal, Vegard; Moen, Frode; Sandbakk, Øyvind (Frontiers in Physiology, 2018)
Nordic combined requires high technical skills and vertical impulse for the ski jumping event and aerobic endurance, ski efficiency and finish-sprint abilities to succeed in the subsequent cross-country race. The main aim of this study was to investigate the development of training, technical, and physiological characteristics during the last 4 seasons preceding the Olympic Games in a Nordic Combined Champion ( 74 kg (63 kg lean-mass)). During the first season of the 4-year cycle, the development of lower-body muscle-mass and vertical jump velocity was prioritized, after which the emphasis on developing the technical abilities were increased over the following three seasons. While maintaining his vertical velocity in countermovement jump at 3 m·s-1, despite an increase of 7 kg overall body-mass, the participant improved his vertical velocity in sport-specific ski jump imitation with 0.31 m·s-1 coincidentally with high technical focus, including use of systematic mental training to enhance skill acquisition, and an almost twofold increase of annual imitation jumps in the four-season cycle. Endurance training increased from 462 hours·season-1 in season one to 635 hours·season-1 in season three, which was mainly due to more low-intensity training. Thereafter, endurance training in the Olympic season was reduced by 12% and more focus was placed on quality of each session and sufficient recovery. The highest V ̇O2peak (5.36 L·min-1 and 72.0 ml·kg-1·min-1) was measured in the third season and thereafter maintained, although competition results were further improved towards the Olympics. The amount of moderate- (31.9±2.8 hours·season-1, 43.0±3.9 sessions·season-1) and high-intensity (28.3±3.1 hours·season-1, 52.3±2.7 sessions·season-1) endurance training was stable throughout the four-season period, with >65% being performed as skiing or roller ski skating. Development of finish-sprint ability was an important strategy throughout the entire period, and both Olympic gold medals were won in a finish-sprint. Altogether, this study provides unique data from the four-season cycle of a two-time Olympic gold medal winner in Nordic Combined, where high amounts ofstrength/power and endurance training is successfully combined towards a peak in the Olympic season. This knowledge shows how the combination of long-term endurance and strength/power may be optimized, and generates new hypotheses to be tested in future research.